A Comprehensive Assessment Plan for Medical Laboratory Science Programs. - AZIZ, HASSAN A.; TILLE, PATRICIA (Clinical Laboratory Science)
Medical laboratory science and medical laboratory technician educational programs are the major provider for well-trained, quality laboratory professionals. These programs, responsible for designing the curriculum that includes up-to-date information regarding the methods, skills, and knowledge that are aligned with the dynamic advancing healthcare field, prepare students to complete a national certification examination. The curriculum, aligned with the program mission and goals, provides course objectives and student learning outcomes that are used to evaluate the student's level of achievement. Evaluation of student achievement is one of the tools to assess program effectiveness. This article provides a comprehensive overview of the necessary components and assessment strategy to design a laboratory science education program that meets the accreditation standards for the National Accreditation Agency for Clinical Laboratory Sciences.